ANALISIS METABOLIT SEKUNDER DARI KALUS RAMBUTAN Nephelium lappaceum L - Fahrauk Faramayuda; Elfahmi Elfahmi; Weni Widy Astuti (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2021)
Rambutan plant (Nephelium lappaceum L.) is a member of the Sapindaceae family. The rambutan plant is one of the natural ingredients that can be developed as traditional medicine. Rambutan peel has the potential for good antioxidant and anticancer activity. Rambutan fruit does not grow every time it needs efforts to produce the active substance in rambutan, using plant tissue culture techniques. The use of the correct variety of mediums and hormones at the right concentration is the key to thriving tissue culture. Explants derived from rambutan leaves were planted precisely on solid media Murashige and Skoog (MS) and WoddyPlant Medium (WPM) containing Indole-3-Butyric Acid (IBA) and Kinetin. After seven days, the callus was subcultured, then after 35 days, the subculture callus was collected and dried. Dry callus and rambutan leaves (Wild type) were macerated with n-hexane, ethyl acetate, and ethanol. The concentrated extract was then applied to a GF 254 silica gel plate with the mobile phase Toluene-Acetone (7: 3) and n-hexane-EthylAsetate (3: 7). The results showed that the concentration of IBA 2 ppm and kinetin three ppm was the best combination because it produced callus. TLC results of rambutan leave with plant tissue culture containing flavonoids and triterpenoids. This study provides new information regarding the induction of rambutan callus and can become the basis for producing active metabolites in rambutan with cell suspension culture development.